Riding the Wave of Innovation: A Qualitative Analysis of Public Transport Drivers' Adaptation to Online-Based Transportation Services - Romadhona, Mochamad Kevin; Oktafenanda, Rachmat Dimas; Kim, Seokkyu; Elkhashab, Noureldin Samy (Universitas Airlangga, 2024)
Transportation Moda growing with various innovations created by people who see business opportunities. Online application-based transportation makes it easier for people to order vehicles to reach their destinations. Such as Go-jek with motorcycle taxi services for two-wheeled vehicles that will take passengers anywhere according to regional boundaries, go-food services or ordering food, and go-car to take passengers with four-wheeled vehicles or cars. This study uses qualitative research methods by looking at reality not only in one meaning. Qualitative research in general can be used for research on people's lives, history, behavior, organizational functionalization, social activities, and others. The result of this study is that the survival mechanism among public transport drivers is by way of debt and maximizing the income earned.